ANALYSIS FOR STUDENTS LEARNING MOTIVATION IN SMAN 1 BAITUSSALAM AND SMAN 1 KRUENG BARONA JAYA OF ACEH BESAR REGENCY FOR BIOLOGY LESSONS - Hamama, Syarifah Farissi; Maulida, Maulida; Mardiana, Mardiana (Jurnal Biologi Sains dan Kependidikan, 2022)
Research has been carried out regarding the level of student motivation in Biology subjects. The purpose of this study was to compare the level of learning motivation between students of SMAN 1 Baitussalam and SMAN 1 Krueng Barona Jaya Aceh Besar, in Biology subject. The population in this study amounted to 315 students, with a sample of 76 students. The method used in this research was descriptive quantitative. The instrument used in this study was a motivational questionnaire for biology subjects. Data analysis was performed using t-test statistics. The results showed that there was no significant comparison between the level of motivation to learn biology subjects between students of SMAN 1 Baitussalam and SMAN 1 Krueng Barona Jaya (t t table = -0.14 1.99254).